Non-Traumatic Intraventricular Hemorrhage With Hydrocephalus - Hafidz, Rosha Aulia Fadhilah; Berlianza, El Varel Baby (Poltekkes Kemenkes Kendari, 2023)
Background: Non-traumatic intracerebral hemorrhage (ICH) in younger population is a relatively rare event but is associated with considerable mortality and poor functional outcome. Imaging plays a crucial role in determining the underlying cause and guide treatment of ICH. Method: A 67-year-old man was brought by his family members to Royal Taruma Hospital emergency department in an unconscious state. The patient has been unconscious for almost 4.5 hours before presenting to the hospital. Before the incidence, the patient was claimed to be normal and able to carry out daily activities normally. The patient had a history of hypertension, diabetes mellitus, and ischaemic stroke (exact history of disease couldn’t be assessed due to guardian’s inability to recall ), and has stopped going for monthly follow-up appointments due to personal reasons. Result: On physical examination, the patient was comatose with GCS of 6 (E1M3V2), vital signs were measured and results are as follow : blood pressure 208/133 mmHg, pulse 98 x/min, respiration rate 16x/min, temperature 36.6°c, oxygen saturation 98%. Cranial nerve examination revealed isochore pupils, with diameters of 3 mm, light reflex (+). Laboratory examination results were as follow : Hemoglobin 15.3 mg/dL, leucocytes 198500/ uL, hematocrit 4%, thrombocytes 248000/uL, erythrocyte sedimentation rate (ESR) 10 mm/hour. Renal and liver functions were within normal limits. Blood glucose was found elevated to 226 mg/dL. Electrolytes, including calcium, sodium, potassium, chloride were within normal limits. Magnesium was decreased to 1.6 mg/dL. Conclusion: Hydrocephalus is very sensitive for detecting the underlying structural and local causes of ICH in young adults. Thus, Hydrocephalus should be considered in the diagnostic work-up of all young Hydrocephalus patients to enable targeted secondary prevention